Co-Movements of the Indian Stock Market with Other Stock Markets: Implications for Portfolio Diversification - Meric, Gulser; Pati, Niranjan; Meric, Ilhan (Indian Journal of Finance, 2011)
In this paper, the researchers have studied the co-movements of the Indian stock market with thirteen other stock markets before, during, and after the 2008 financial/economic crisis. The findings indicate that there is considerable time-varying volatility in the correlation of the Indian stock market with the other stock markets. The trend analysis results show that correlations between the Indian stock market and the other stock markets have been increasing, which suggest that the benefits of global portfolio diversification have been decreasing. The researchers found three statistically significant principal components in terms of the similarities of the co-movement patterns of the Indian stock market, with the other stock markets. Investors in the Indian stock market could maximize their global diversification benefit by investing in the stock markets with the highest factor loadings in the three different principal components during the May 15, 2006-August 5, 2010 period. The Granger-causality test results show that the U.S., Hong Kong, New Zealand, and Australian stock markets can predict the returns of the Indian stock market. The Indian stock market, in turn, can predict the returns of the Malaysian, Indonesian, South Korean, Taiwanese, Hong Kong, and German stock markets at conventional significance levels. This research has significant implications for portfolio diversification decisions.